Treatment of bipolar disorders - The use of supplements (Engrami, 2023)
In recent years, there has been increasing interest regarding the use of supplements as adjuvant therapy in treatment of various psychiatric disorders. Supplements are seen as a complement to traditional pharmacotherapeutic and psychotherapeutic approaches, providing a more personalized approach to treatment. There is a large body of research that has investigated their potential impact on various biological processes, such as neurogenesis, neuro progression, oxidative stress, inflammation, mitochondrial dysfunction and others. Although evidence of effectiveness of supplements in treating psychiatric disorders is still evolving, there is a growing number of scientific studies that support their potential benefits. The integrative modern therapeutic approach increasingly includes the use of supplements as adjuvant therapy, considering the complexity of clinical presentation of disorder. This article will present the interest in the use of supplements in the treatment of bipolar disorder, as well as potential benefits. Evidence (or lack thereof) regarding the most significant and most researched supplements will also be provided, along with the perspective and role of supplements in bipolar disorder.
Keywords: bipolar disorder; supplements; staging; neuroprogression